CULTURAL FACTORS IMPACTING MANAGEMENT OF RESOURCES OF EARLY CHILDHOOD EDUCATION IN NDOTO EAST, SAMBURU NORTH SUB COUNTY - LETIWA CHRISTOPHER KURENI, (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
MERU UNIVERSITY OF SCIENCE AND TECHNOLOGY P.O. Box 972-60200 Meru-Kenya Phone: +254 712524293, +254 799529958, +254 799529959 Email: info@must.ac.ke Website: www.must.ac.ke TITLE: CULTURAL FACTORS IMPACTING MANAGEMENT OF RESOURCES IN EARLY CHILDHOOD EDUCATION IN NDOTO EAST, SAMBURU NORTH SUB-COUNTY SUB-THEME: EDUCATION AUTHORS: LETIWA CHRISTOPHER KURENI SUPERVISORS: Prof KAGENI NJAGI DR TIRUS MUTWIRI AFFILIATION: MERU UNIVERSITY OF SCIENCE & TECHNOLOGY Contact: Email: letiwachriz@gmail.com Telephone: +254 707633697 ABSTRACT This study investigates the cultural factors influencing the management of resources in Early Childhood Education (ECE) within Ndoto east ,Samburu North, Sub-county. The problem statement identifies the challenges arising from the interplay between traditional cultural norms and modern educational practices, hindering effective resource management in ECDE settings. The objectives of the study are to examine how cultural beliefs, practices, and values impact resource allocation and utilization in ECDE, and to identify strategies for mitigating these challenges to enhance ECDE outcomes. The target population includes ECDE educators, community leaders, parents, and government officials directly involved in or affected by ECDE initiatives in Ndoto east ,Samburu North Sub-county. The sampling technique employed will be purposive sampling, selecting participants based on their relevance to the research objectives and their experience in ECDE management. A sample size of 50 participants will be selected to ensure diverse perspectives and comprehensive data collection. Data collection will be conducted through semi-structured interviews, focus group discussions, and document analysis. The instruments used will include interview guides, observation checklists, and document review templates, tailored to capture information relevant to the study objectives. Data analysis will follow a qualitative approach, involving thematic coding and content analysis. Transcribed interviews, focus group discussions, and document extracts will be analyzed to identify recurring themes and patterns related to cultural factors influencing resource management in ECDE. The findings will provide insights into effective strategies for addressing cultural barriers and optimizing resource utilization in ECDE settings within Ndoto east ,Samburu North Sub-county.